Copper pyrovanadate-based reinforcement for reducing thermal expansion coefficient of composite material and preparation method of copper pyrovanadate-based reinforcement

CN119263828AActive Publication Date: 2025-01-07HARBIN INST OF TECH
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411683718.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-01-07
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

[0004]本发明为了解决现有的焦钒酸铜基增强体β-Cu2V2O7负热膨胀性能较差且不具有零膨胀性的问题,提出了降低复合材料热膨胀系数的焦钒酸铜基增强体及其制备方法

Benefits of technology

[0018] 1. The present invention uses solid phase sintering to prepare β-Cu 2-x Ba x V 2 O 7 (01.9 Ba 0.1 V 2 O 7 It shows zero expansion effect in the temperature range of 173-473K. Adding this reinforcement during the preparation of composite materials can reduce the thermal expansion coefficient of the composite material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263828A_ABST
    Figure CN119263828A_ABST
Patent Text Reader

Abstract

The invention discloses a copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of a composite material and a preparation method of the copper pyrovanadate-based reinforcement, and relates to a copper pyrovanadate-based reinforcement and a preparation method of the copper pyrovanadate-based reinforcement. The invention aims to solve the problem that the existing copper pyrovanadate-based reinforcement beta-Cu2V2O7 has poor negative thermal expansion performance and does not have zero expansibility. The copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material is beta-Cu2-xBaxV2O7, wherein x is more than 0 and less than or equal to 0.2; and the beta-Cu (2-x) BaxV2O7 is a zero-expansion ceramic. Another copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material is beta-Cu2-xMnxV2O7, wherein x is more than 0 and less than 2; and beta-Cu (2-x) MnxV2O7 is a negative thermal expansion material. The beta-Cu2-xBaxV2O7 solid solution can be prepared through solid-phase sintering, the preparation process is simple, sintering of a large number of products can be achieved at a time, and no harmful gas is released. And a simpler and more efficient technical means is provided for successfully preparing the beta-Cu2-xBaxV2O7 solid solution through solid-phase sintering in cooperation with rapid cooling and batch synthesis of the beta-Cu2-xBaxV2O7 solid solution. The mechanical property of the prepared sample is greatly improved compared with that of beta-Cu2V2O7, and the prepared sample has the potential of being independently used as a structural part.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of a composite material and a preparation method thereof. Background Art

[0002] In recent years, the rapid development of aerospace, precision instruments, electronic communications and other fields has put forward higher requirements on the stability, reliability and service life of many functional structures and components. In particular, when facing large changes in ambient temperature during service, the mismatch of thermal expansion coefficients between different components will inevitably lead to thermal stress, and under the action of long-term mechanical fatigue and creep, it may even cause material structure damage, greatly reducing the service life of the material. Therefore, the development of material systems with adjustable thermal expansion coefficients to avoid or reduce the thermal mismatch phenomenon between materials has become an issue that cannot be ignored in the field of engineering applications.

[0003] The discovery of negative thermal expansion materials provides ideas for solving the above problems. A large number of studies have shown that the thermal expansion properties of manganese nitrogen compounds and oxides can be changed through chemical regulation. From the perspective of stability and practical application, the oxide system has greater development potential. In recent years, Cu2V2O7 has come into people's attention. It has three crystal structures, namely orthorhombic α phase, monoclinic β phase and triclinic γ phase. The α phase has almost no negative thermal expansion effect, and the γ phase is a metastable phase and difficult to exist stably. The negative thermal expansion range of pure phase β-Cu2V2O7 is 153-573K, and the thermal expansion coefficient α v =-2.7×10 -6 ~10.7×10 -6 K -1 (323-573K), so only the β phase has the development potential of performance regulation, but in its preparation process, impurities such as the α phase often exist when the cooling rate is low. In addition, from the perspective of material performance requirements, people hope to directly obtain materials with zero expansion effect, or prepare materials with large negative thermal expansion effect, and prepare zero expansion composite materials by compounding with metals. As for pure phase β-Cu2V2O7, its negative thermal expansion performance is not ideal. Its thermal expansion coefficient is only -2.7×10- -6 K -1 , which is somewhat different from zero expansion, and is much higher than the thermal expansion coefficient of ZrW2O8 (-21.9×10 -6 K -1 ), which is not conducive to the preparation of zero-expansion composite materials. Therefore, β-Cu2V2O7 has poor negative thermal expansion performance and does not have zero expansion, which limits the application of β-Cu2V2O7. If it is possible to adjust the thermal expansion performance of the material by introducing other element ions, it will have great scientific research potential and application space. Summary of the invention

[0004] In order to solve the problem that the existing copper pyrovanadate-based reinforcement β-Cu2V2O7 has poor negative thermal expansion performance and does not have zero expansion, the present invention provides a copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of a composite material and a preparation method thereof.

[0005] The copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material is β-Cu 2-x Ba x V2O7, 0<x≤0.2; β-Cu 2-x Ba x V2O7 is a zero expansion ceramic.

[0006] The invention discloses a pyrovanadate copper-based reinforcement β-Cu 2-x Ba x The preparation method of V2O7 is carried out according to the following steps:

[0007] 1. Weighing materials:

[0008] According to β-Cu 2-x Ba x The molar ratio of elements in V2O7 is Cu raw material, V raw material and Ba raw material as raw materials; wherein 0<x≤0.2

[0009] The Cu raw material is CuO or a decomposable copper-containing compound, and the decomposable copper-containing compound is CuCO3, Cu(OH)2 or Cu2(OH)2CO3;

[0010] The Ba raw material is barium oxide or a Ba compound, and the Ba compound is barium hydroxide or barium carbonate;

[0011] The V raw material is V2O5 or a decomposable vanadium-containing compound, and the decomposable vanadium-containing compound is VO2(C2O4)·2H2O or NH4VO3;

[0012] 2. Powder mixing:

[0013] The raw materials weighed in step 1 are mixed and added into anhydrous ethanol, wet-mixed and ball-milled with anhydrous ethanol as the medium, and then dried to obtain a mixed powder;

[0014] 3. Powder sintering:

[0015] The dried mixed powder is sintered at high temperature and then cooled quickly to complete the process;

[0016] The high temperature sintering process is as follows: sintering temperature is 600-900°C; heating rate is 3-50°C / min; holding time is 180-1200min; sintering atmosphere is vacuum, air, argon, nitrogen or helium; cooling method is quenching;

[0017] The present invention has the following beneficial effects:

[0018] 1. The present invention adopts solid phase sintering to prepare β-Cu 2-x Ba x V2O7 (0<x≤0.2) solid solution is a zero expansion ceramic. 1.9 Ba 0.1 V2O7 exhibits a zero expansion effect in the temperature range of 173-473K. Adding this reinforcement during the preparation of composite materials can reduce the thermal expansion coefficient of the composite materials.

[0019] 2. The present invention can prepare β-Cu by solid phase sintering 2-x Ba x V2O7 solid solution has a simple preparation process, can achieve a large number of products in a single sintering, and no harmful gas is released. 2-x Ba x The V2O7 solid solution is regarded as part of the Cu in Cu2V2O7 2+ Ba 2+ The compound formed by replacing 2+ The ionic radius of Ba is about 73 pm, while 2+ The ion radius of the ions is about 135pm, and the radius of the latter is nearly twice that of the former. From the perspective of stability, the greater the difference in radius between the replacing ions and the replaced ions, the greater the degree of lattice distortion of the formed compound, the more unstable the system, and the more difficult it is to prepare the material. When the difference in radius between the two ions is too large, the traditional methods usually adopt the following methods: the sol-gel method has the problems of complex preparation process and impurities in the product; the combustion synthesis method has the problems of difficult control of the preparation process and the generation of harmful gases; the co-deposition doping has the problems of high equipment requirements, complex process and low yield. The present invention successfully realizes β-Cu by solid-phase sintering combined with rapid cooling. 2-x Ba x The preparation of V2O7 solid solution provides a simpler and more efficient technical means for its batch synthesis.

[0020] 3. The present invention solves the problem of the presence of α phase and other impurities in the sample when the cooling rate is low by quenching and rapid cooling, and prepares pure single-phase β-Cu 2-x Ba x V2O7 solid solution, and the sample crystal structure is kept as C2 / c monoclinic structure.

[0021] 4. The existing β-Cu2V2O7 is difficult to sinter. Even after high-temperature treatment, it is difficult for the ceramic particles to form an effective bond. The sintered sample still exists in the form of powder. 2-x Bax V2O7 ceramics greatly improve the sintering properties of the base ceramics, and the mechanical properties of the prepared samples are greatly improved compared with β-Cu2V2O7. For example, β-Cu 1.9 Ba 0.1 The hardness of V2O7 reaches 404.5±3.6HV, and it has the potential to be used independently as a structural component.

[0022] Another copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material of the present invention is β-Cu 2-x Mn x V2O7, 0<x<2; β-Cu 2-x Mn x V2O7 is a negative thermal expansion material.

[0023] The β-Cu 2-x Mn x The preparation method of V2O7 is carried out according to the following steps:

[0024] 1. Weighing materials:

[0025] According to β-Cu 2-x Mn x The molar ratio of elements in V2O7, Cu raw material, V raw material and Mn raw material are weighed as raw materials; wherein 0<x<2;

[0026] The Cu raw material is CuO or a decomposable copper-containing compound, and the decomposable copper-containing compound is CuCO3, Cu(OH)2 or Cu2(OH)2CO3;

[0027] The Mn raw material is MnO or a Mn compound, and the Mn compound is manganese hydroxide or manganese carbonate;

[0028] The V raw material is V2O5 or a decomposable vanadium-containing compound, and the decomposable vanadium-containing compound is VO2(C2O4)·2H2O or NH4VO3;

[0029] 2. Powder mixing:

[0030] The raw materials weighed in step 1 are mixed and added into anhydrous ethanol, wet-mixed and ball-milled with anhydrous ethanol as the medium, and then dried to obtain a mixed powder;

[0031] 3. Powder sintering:

[0032] The dried mixed powder is sintered at high temperature and then rapidly cooled to complete the process;

[0033] The high temperature sintering process is as follows: the sintering temperature is 600-900°C; the heating rate is 1-50°C / min; the holding time is 180-1200min; the sintering atmosphere is vacuum, air, argon, nitrogen or helium; the cooling method is quenching;

[0034] The present invention has the following beneficial effects:

[0035] 1. The present invention prepares β-Cu by solid phase sintering 2-x Mn x V2O7 solid solution has a simple preparation process, large synthesis volume, and no harmful gas is released during the process. 1.8 Mn 0.2 The thermal expansion coefficient of V2O7 remains unchanged at low temperatures. The thermal expansion coefficient of the sample in the range of 573-773K is α v =-20.5×10 -6 K -1 , and β-Cu2V2O7(α v =-10.7×10 -6 K -1 ), the negative thermal expansion effect is significantly improved. Adding this reinforcement in the process of preparing the composite material can reduce the thermal expansion coefficient of the composite material.

[0036] 2. The present invention solves the problem of the presence of α phase and other impurities in the sample when the cooling rate is low by quenching and rapid cooling, and prepares a single-phase β-Cu 2-x Mn x V2O7 solid solution, and the sample crystal structure is kept as C2 / c monoclinic structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 The β-Cu prepared in Example 1 1.9 Ba 0.1 XRD patterns of V2O7 at different temperatures;

[0038] Figure 2 The β-Cu prepared in Example 1 1.9 Ba 0.1 The curve of the unit cell volume of V2O7 changing with temperature;

[0039] Figure 3 The β-Cu prepared in Example 2 1.8 Mn 0.2 XRD patterns of V2O7 at different temperatures;

[0040] Figure 4 The β-Cu prepared in Example 2 1.8 Mn 0.2 The curve of the unit cell volume of V2O7 changing with temperature. DETAILED DESCRIPTION

[0041] The technical solution of the present invention is not limited to the specific implementation modes listed below, but also includes any reasonable combination of the specific implementation modes.

[0042] Specific implementation method 1: In this implementation method, the copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material is β-Cu 2-x Ba x V2O7, 0<x≤0.2; β-Cu 2-x Ba x V2O7 is a zero expansion ceramic.

[0043] In this embodiment, β-Cu 2-x Ba x V2O7 (0<x≤0.2) solid solution is a zero expansion ceramic. 1.9 Ba 0.1 V2O7 exhibits zero expansion effect in the temperature range of 173-473K. 2-x Ba x V2O7 ceramics greatly improve the sintering properties of the base ceramics, and the mechanical properties of the prepared samples are greatly improved compared with β-Cu2V2O7. For example, β-Cu 1.9 Ba 0.1 The hardness of V2O7 reaches 404.5±3.6HV, and it has the potential to be used independently as a structural component.

[0044] Specific embodiment 2: This embodiment reduces the thermal expansion coefficient of the composite material by using the copper pyrovanadate-based reinforcement β-Cu 2-x Ba x The preparation method of V2O7 is carried out according to the following steps:

[0045] 1. Weighing materials:

[0046] According to β-Cu 2-x Ba x The molar ratio of elements in V2O7 is Cu raw material, V raw material and Ba raw material as raw materials; wherein 0<x≤0.2

[0047] The Cu raw material is CuO or a decomposable copper-containing compound, and the decomposable copper-containing compound is CuCO3, Cu(OH)2 or Cu2(OH)2CO3;

[0048] The Ba raw material is barium oxide or a Ba compound, and the Ba compound is barium hydroxide or barium carbonate;

[0049] The V raw material is V2O5 or a decomposable vanadium-containing compound, and the decomposable vanadium-containing compound is VO2(C2O4)·2H2O or NH4VO3;

[0050] 2. Powder mixing:

[0051] The raw materials weighed in step 1 are mixed and added into anhydrous ethanol, wet-mixed and ball-milled with anhydrous ethanol as the medium, and then dried to obtain a mixed powder;

[0052] 3. Powder sintering:

[0053] The dried mixed powder is sintered at high temperature and then cooled quickly to complete the process;

[0054] The high temperature sintering process is as follows: the sintering temperature is 600-900°C; the heating rate is 3-50°C / min; the holding time is 180-1200min; the sintering atmosphere is vacuum, air, argon, nitrogen or helium; and the cooling method is quenching.

[0055] 1. This embodiment adopts solid phase sintering to prepare β-Cu 2-x Ba x V2O7 (0<x≤0.2) solid solution is a zero expansion ceramic. 1.9 Ba 0.1 V2O7 exhibits a zero expansion effect in the temperature range of 173-473K. Adding this reinforcement during the preparation of composite materials can reduce the thermal expansion coefficient of the composite materials.

[0056] 2. This embodiment can prepare β-Cu by solid phase sintering 2-x Ba x V2O7 solid solution has a simple preparation process, can achieve a large number of products in a single sintering, and no harmful gas is released. 2-x Ba x The V2O7 solid solution is regarded as part of the Cu in Cu2V2O7 2+ Ba 2+ The compound formed by replacing 2+ The ionic radius of Ba is about 73 pm, while 2+ The ion radius of the ions is about 135pm, and the radius of the latter is nearly twice that of the former. From the perspective of stability, the greater the difference in radius between the replacing ions and the replaced ions, the greater the degree of lattice distortion of the formed compound, the relatively more unstable the system, and the greater the difficulty in material preparation. When the difference in the radius of the two ions is too large, the traditional methods usually adopt the following methods: the sol-gel method has the problems of complex preparation process and impurities in the product; the combustion synthesis method has the problems of difficult control of the preparation process and the generation of harmful gases; the co-deposition doping has the problems of high equipment requirements, complex process and low yield. This implementation method successfully realizes β-Cu by solid-phase sintering combined with rapid cooling. 2-x Ba xThe preparation of V2O7 solid solution provides a simpler and more efficient technical means for its batch synthesis.

[0057] 3. This embodiment solves the problem of the presence of α phase and other impurities in the sample when the cooling rate is low by quenching and rapid cooling, and prepares pure single-phase β-Cu 2-x Ba x V2O7 solid solution, and the sample crystal structure is kept as C2 / c monoclinic structure.

[0058] 4. The existing β-Cu2V2O7 is difficult to sinter. Even after high temperature treatment, it is difficult for the ceramic particles to form an effective bond. The sintered sample still exists in the form of powder. 2-x Ba x V2O7 ceramics greatly improve the sintering properties of the base ceramics, and the mechanical properties of the prepared samples are greatly improved compared with β-Cu2V2O7. For example, β-Cu 1.9 Ba 0.1 The hardness of V2O7 reaches 404.5±3.6HV, and it has the potential to be used independently as a structural component.

[0059] Specific implementation method three: This implementation method is different from specific implementation method two in that: the purity of the Cu raw material, V raw material and Ba raw material in step one is 98-99.99%, and the average particle size is 0.1-500 μm.

[0060] Specific implementation method 4: This implementation method is different from specific implementation method 2 in that the mass of the anhydrous ethanol in step 2 is 0.2-3 times the mass of the raw material.

[0061] Specific implementation method five: This implementation method is different from specific implementation method two in that: the wet mixing ball milling process in step two is: the ball-to-material ratio is (1-20):1, the rotation speed is 20-100rpm, and the time is 4-72h.

[0062] Specific embodiment 6: In this embodiment, the copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material is β-Cu 2-x Mn x V2O7, 0<x<2; β-Cu 2-x Mn x V2O7 is a negative thermal expansion material.

[0063] The β-Cu prepared by solid phase sintering in this embodiment 2-x Mn x V2O7 solid solution is a negative thermal expansion material, where β-Cu 1.8 Mn 0.2 The thermal expansion coefficient of V2O7 remains unchanged at low temperatures. The thermal expansion coefficient of the sample in the range of 573-773K is αv =-20.5×10 -6 K -1 , and β-Cu2V2O7(α v =-10.7×10 -6 K -1 ), the negative thermal expansion effect is significantly improved.

[0064] Specific implementation method seven: β-Cu 2-x Mn x The preparation method of V2O7 is carried out according to the following steps:

[0065] 1. Weighing materials:

[0066] According to β-Cu 2-x Mn x The molar ratio of elements in V2O7, Cu raw material, V raw material and Mn raw material are weighed as raw materials; wherein 0<x<2;

[0067] The Cu raw material is CuO or a decomposable copper-containing compound, and the decomposable copper-containing compound is CuCO3, Cu(OH)2 or Cu2(OH)2CO3;

[0068] The Mn raw material is MnO or a Mn compound, and the Mn compound is manganese hydroxide or manganese carbonate;

[0069] The V raw material is V2O5 or a decomposable vanadium-containing compound, and the decomposable vanadium-containing compound is VO2(C2O4)·2H2O or NH4VO3;

[0070] 2. Powder mixing:

[0071] The raw materials weighed in step 1 are mixed and added into anhydrous ethanol, wet-mixed and ball-milled with anhydrous ethanol as the medium, and then dried to obtain a mixed powder;

[0072] 3. Powder sintering:

[0073] The dried mixed powder is sintered at high temperature and then rapidly cooled to complete the process;

[0074] The high temperature sintering process is as follows: sintering temperature is 600-900°C; heating rate is 1-50°C / min; holding time is 180-1200min; sintering atmosphere is vacuum, air, argon, nitrogen or helium; cooling method is quenching.

[0075] 1. This embodiment prepares β-Cu by solid phase sintering 2-x Mn x V2O7 solid solution has a simple preparation process, large synthesis volume, and no harmful gas is released during the process. 1.8 Mn0.2 The thermal expansion coefficient of V2O7 remains unchanged at low temperatures. The thermal expansion coefficient of the sample in the range of 573-773K is α v =-20.5×10 -6 K -1 , and β-Cu2V2O7(α v =-10.7×10 -6 K -1 ), the negative thermal expansion effect is significantly improved. Adding this reinforcement in the process of preparing the composite material can reduce the thermal expansion coefficient of the composite material.

[0076] 2. This embodiment solves the problem of the presence of α phase and other impurities in the sample when the cooling rate is low by quenching and rapid cooling, and prepares a single-phase β-Cu 2-x Mn x V2O7 solid solution, and the sample crystal structure is kept as C2 / c monoclinic structure.

[0077] Specific implementation eight: This implementation differs from specific implementation seven in that: in step one, the purity of the Cu raw material, the V raw material and the Mn raw material is 98-99.99%, and the average particle size is 0.1-500 μm.

[0078] Specific embodiment 9: This embodiment is different from specific embodiment 7 in that the mass of anhydrous ethanol in step 2 is 0.2-3 times the mass of the raw material. The wet mixing ball milling process in step 2 is: the ball-to-material ratio is (1-20):1, the rotation speed is 20-100rpm, and the time is 4-72h.

[0079] Specific embodiment ten: This embodiment differs from specific embodiment seven in that: the wet mixing ball milling process in step two is: the ball-to-material ratio is (1-20):1, the rotation speed is 20-100rpm, and the time is 4-72h.

[0080] Embodiment 1:

[0081] The copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material is β-Cu 1.9 Ba 0.1 V2O7; β-Cu 1.9 Ba 0.1 V2O7 is a zero expansion ceramic.

[0082] The invention discloses a pyrovanadate copper-based reinforcement β-Cu 1.9 Ba 0.1 The preparation method of V2O7 is carried out according to the following steps:

[0083] 1. Weighing materials:

[0084] According to β-Cu 1.9 Ba0.1 The molar ratio of each element in V2O7 was used to weigh CuO, V2O5 and BaCO3 as raw materials;

[0085] The purity of the CuO, V2O5 and BaCO3 is 99.99%, and the particle size of CuO is D 50 10μm; the particle size D of V2O5 50 1 μm; the particle size of BaCO3 is D 50 10μm;

[0086] 2. Powder mixing:

[0087] The raw materials weighed in step 1 are mixed and added into anhydrous ethanol, wet-mixed and ball-milled with anhydrous ethanol as the medium, and then dried to obtain a mixed powder;

[0088] The mass of the anhydrous ethanol is 0.5 times the mass of the raw material;

[0089] The wet mixing ball milling process is as follows: the ball-to-material ratio is 2:1, the rotation speed is 80 rpm, and the time is 24 hours;

[0090] 3. Powder sintering:

[0091] The dried mixed powder is sintered at high temperature and then rapidly cooled to complete the process;

[0092] The high temperature sintering process is as follows: sintering temperature is 750°C; heating rate is 5°C / min; holding time is 240min; sintering atmosphere is air atmosphere; cooling method is quenching;

[0093] from Figure 1 It can be seen that within the test temperature range, the diffraction peaks of the samples are in good agreement with β-Cu2V2O7, which proves that this embodiment successfully produced high-purity β-Cu by solid-phase sintering and rapid cooling. 1.9 Ba 0.1 V2O7 single-phase solid solution, on the other hand, proves that the crystal structure of the sample does not change within the test temperature range. In other words, although Ba 2+ The introduction of β-Cu leads to a large degree of lattice distortion, but 1.9 Ba 0.1 V2O7 can still exist stably within the test temperature range. The change law of unit cell volume with temperature is calculated based on the lattice constant and crystal face angle. Figure 2 As shown in the figure, it can be seen that in the range of 173-373K, the volume of the sample unit cell does not change much. According to calculations, the average thermal expansion coefficient α of the sample in this temperature range is v About 0.44×10 -6 K -1In other words, the sample exhibits a zero expansion effect in the temperature range of 173-473K, and the decrease in the thermal expansion coefficient of the sample at high temperature is also consistent with the law of lattice constant change.

[0094] Embodiment 2:

[0095] The copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material in this embodiment is β-Cu 1.8 Mn 0.2 V2O7, β-Cu 1.8 Mn 0.2 V2O7 is a negative thermal expansion material.

[0096] The β-Cu 1.8 Mn 0.2 The preparation method of V2O7 is carried out according to the following steps:

[0097] 1. Weighing materials:

[0098] According to β-Cu 1.8 Mn 0.2 The molar ratio of each element in V2O7 CuO, MnO and V2O5 were weighed as raw materials;

[0099] The purity of the CuO, MnO and V2O5 is 99.99%, and the particle size of CuO is D 50 10μm; the particle size D of V2O5 50 1 μm; the particle size of MnO is D 50 5μm;

[0100] 2. Powder mixing:

[0101] The raw materials weighed in step 1 are mixed and added into anhydrous ethanol, wet-mixed and ball-milled with anhydrous ethanol as the medium, and then dried to obtain a mixed powder;

[0102] The mass of the anhydrous ethanol is 0.5 times the mass of the raw material;

[0103] The wet mixing ball milling process is as follows: the ball-to-material ratio is 2:1, the rotation speed is 80 rpm, and the time is 24 hours;

[0104] 3. Powder sintering:

[0105] The dried mixed powder is sintered at high temperature and then rapidly cooled to complete the process;

[0106] The high temperature sintering process is as follows: sintering temperature is 730°C; heating rate is 5°C / min; holding time is 240min; sintering atmosphere is air atmosphere; cooling method is quenching;

[0107] Example 2 Preparation of β-Cu 1.8 Mn 0.2V2O7 ceramics can be synthesized in large quantities through solid phase sintering, and the preparation process is simple. Combined with rapid cooling, a single-phase solid solution can be obtained, and the solid solution crystal can maintain a good C2 / c monoclinic structure. 2+ The introduction of can significantly improve and reduce the thermal expansion coefficient of the material at high temperature, among which β-Cu 1.8 Mn 0.2 V2O7 can make the thermal expansion coefficient of the sample in the range of 573-773K without affecting the thermal expansion coefficient at low temperature. v =-20.5×10 -6 K -1 , and β-Cu2V2O7(α v =-10.7×10 -6 K -1 ), the negative thermal expansion effect is significantly improved.

[0108] from Figure 3 It can be seen that within the test temperature range, the diffraction peaks of the samples are in good agreement with β-Cu2V2O7, which proves that the present invention successfully obtains high-purity β-Cu by solid-phase sintering and rapid cooling. 1.8 Mn 0.2 V2O7 single-phase solid solution, on the other hand, proves that within the test temperature range, the sample crystal structure has not changed. According to the lattice constant and crystal face angle, the change law of unit cell volume with temperature is calculated as follows Figure 4 As shown in the figure, it can be seen that in the range of 573-773K, the unit cell volume of the sample decreases rapidly. According to calculations, the average thermal expansion coefficient α of the sample in this temperature range is v About -20.5×10 -6 K -1 , and β-Cu2V2O7(α v =-10.7×10 -6 K -1 ), the negative thermal expansion effect is significantly improved.

Claims

1. A copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of a composite material, characterized in that: The copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material is β-Cu 2-x Ba x V2O7, 0<x≤0.2; β-Cu 2-x Ba x V2O7 is a zero expansion ceramic.

2. The copper pyrovanadate-based reinforcement β-Cu for reducing the thermal expansion coefficient of the composite material according to claim 1 2-x Ba x The preparation method of V2O7 is characterized by: Copper pyrovanadate-based reinforcement β-Cu for reducing thermal expansion coefficient of composites 2-x Ba x The preparation method of V2O7 is carried out according to the following steps:

1. Weighing materials: According to β-Cu 2-x Ba x The molar ratio of elements in V2O7 is Cu raw material, V raw material and Ba raw material as raw materials; wherein 0<x≤0.2 The Cu raw material is CuO or a decomposable copper-containing compound, and the decomposable copper-containing compound is CuCO3, Cu(OH)2 or Cu2(OH)2CO3; The Ba raw material is barium oxide or a Ba compound, and the Ba compound is barium hydroxide or barium carbonate; The V raw material is V2O5 or a decomposable vanadium-containing compound, and the decomposable vanadium-containing compound is VO2(C2O4)·2H2O or NH4VO3; 2. Powder mixing: The raw materials weighed in step 1 are mixed and added into anhydrous ethanol, wet-mixed and ball-milled with anhydrous ethanol as the medium, and then dried to obtain a mixed powder; 3. Powder sintering: The dried mixed powder is sintered at high temperature and then cooled quickly to complete the process; The high temperature sintering process is as follows: the sintering temperature is 600-900°C; the heating rate is 3-50°C / min; the holding time is 180-1200min; the sintering atmosphere is vacuum, air, argon, nitrogen or helium; and the cooling method is quenching.

3. The copper pyrovanadate-based reinforcement β-Cu for reducing the thermal expansion coefficient of the composite material according to claim 2 2-x Ba x The preparation method of V2O7 is characterized by: In step 1, the purity of the Cu raw material, the V raw material and the Ba raw material is 98-99.99%, and the average particle size is 0.1-500 μm.

4. The copper pyrovanadate-based reinforcement β-Cu for reducing the thermal expansion coefficient of the composite material according to claim 2 2-x Ba x The preparation method of V2O7 is characterized by: The mass of the anhydrous ethanol in step 2 is 0.2-3 times the mass of the raw material.

5. The copper pyrovanadate-based reinforcement β-Cu for reducing the thermal expansion coefficient of the composite material according to claim 2 2-x Ba x The preparation method of V2O7 is characterized by: The wet mixing ball milling process in step 2 is as follows: the ball-to-material ratio is (1-20):1, the rotation speed is 20-100 rpm, and the time is 4-72 hours.

6. A copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of a composite material, characterized in that: The copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material is β-Cu 2-x Mn x V2O7, 0<x<2; β-Cu 2-x Mn x V2O7 is a negative thermal expansion material.

7. The copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material according to claim 6 is β-Cu 2-x Mn x The preparation method of V2O7 is characterized by: β-Cu 2-x Mn x The preparation method of V2O7 is carried out according to the following steps:

1. Weighing materials: According to β-Cu 2-x Mn x The molar ratio of elements in V2O7, Cu raw material, V raw material and Mn raw material are weighed as raw materials; wherein 0<x<2; The Cu raw material is CuO or a decomposable copper-containing compound, and the decomposable copper-containing compound is CuCO3, Cu(OH)2 or Cu2(OH)2CO3; The Mn raw material is MnO or a Mn compound, and the Mn compound is manganese hydroxide or manganese carbonate; The V raw material is V2O5 or a decomposable vanadium-containing compound, and the decomposable vanadium-containing compound is VO2(C2O4)·2H2O or NH4VO3; 2. Powder mixing: The raw materials weighed in step 1 are mixed and added into anhydrous ethanol, wet-mixed and ball-milled with anhydrous ethanol as the medium, and then dried to obtain a mixed powder; 3. Powder sintering: The dried mixed powder is sintered at high temperature and then rapidly cooled to complete the process; The high temperature sintering process is as follows: sintering temperature is 600-900°C; heating rate is 1-50°C / min; holding time is 180-1200min; sintering atmosphere is vacuum, air, argon, nitrogen or helium; cooling method is quenching.

8. The copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material according to claim 7 is β-Cu 2- x Mn x The preparation method of V2O7 is characterized by: In step 1, the purity of the Cu raw material, the V raw material and the Mn raw material is 98-99.99%, and the average particle size is 0.1-500 μm.

9. The copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material according to claim 7 is β-Cu 2- x Mn x The preparation method of V2O7 is characterized by: The mass of the anhydrous ethanol in step 2 is 0.2-3 times the mass of the raw material.

10. The copper pyrovanadate-based reinforcement for reducing the thermal expansion coefficient of the composite material according to claim 7 is β-Cu 2- x Mn x The preparation method of V2O7 is characterized by: The wet mixing ball milling process in step 2 is as follows: the ball-to-material ratio is (1-20):1, the rotation speed is 20-100 rpm, and the time is 4-72 hours.

Citation Information

Patent Citations

  • Visible light responsible photo-catalyst BaCuV2O7 and preparation method thereof

    CN103331169A

  • Method for preparing near-zero thermal expansion ZrO2 / ZrW2O8 composite material

    CN106565236A

  • Negative thermal expansion material and composite material

    CN118715181A

  • Negative thermal expansion material and composite material

    JP2023123327A

  • Negative thermal expansion material and composite material

    JP2023123341A